PENINGKATAN HASIL BELAJAR MATERI MEMBACA WAKTU MENGGUNAKAN MEDIA BENDA NYATA PADA SISWA KELAS II SDN SUMBER KEJAYAN 01 KECAMATAN MAYANG - Mohamad Aldy Rozikin; Putera, Rafhi Febryan (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Implementation of Learning Improvement is carried out because the achievement of student learning outcomes is still less than the KKM. This is because many students only pay attention, listen to explanations, absorb and accept the new information they receive, then record and memorize it and work on the practice questions given by the teacher. The author's goal in carrying out this research report is to improve student learning outcomes in grade II by implementing learning using real object media while reading material at SDN Sumber Kejayan 01. Assessment of learning activities is in the form of written tests and observations. The score sheet is in the form of individual scores, namely an increase in mastery results from cycle I with 14 students or 77.77% completeness, in cycle II it increases to 18 students or 100%. This shows an increase in mastery in the class has achieved mastery by using real object media. Keywords: Learning Outcomes, Reading Time, Media, Real Objects